A large dentigerous cyst treated with decompression and orthosurgical traction: A case report - Nascimento, Rodrigo Dias [UNESP]; Raldi, Fernando Vagner [UNESP]; De Moraes, Michelle Bianchi [UNESP]; Cardoso, Paula Elaine [UNESP]; Holleben, Deborah [UNESP] (My University, 2015)
This article presents the case of an 8-year-old patient who presented with a large radiolucency associated with the maxillary left canine and a supernumerary tooth. A computed tomography scan showed the radiolucency was in close proximity to the roots of the anterior teeth, with no areas of root resorption, and expansion into the left maxillary sinus. The boundaries of the maxillary sinus floor were still preserved. After positive aspiration of intralesional liquid and due to the large size of the radiolucency, a decompression technique was selected to preserve the permanent canine. Surgery was performed to remove the supernumerary tooth, followed by orthodontic treatment and surgery to allow access for orthodontic traction of the permanent canine. More than 5 years post-treatment, no recurrence was observed and the therapeutic option to position and preserve the permanent canine was successful.
Keywords: Decompression; Dentigerous cyst; Eruption of teeth; Unerupted maxillary canine